Consumers’ Decision-Making and Role of Social Media Influencers in the UK Hotel Industry - Haque, Mohammad Mahbubul; Hasan, Rahaman; Kumar, Anuj (Indian Journal of Marketing, 2025)
Purpose : The present study examined the role of social media influencers in shaping consumer decision-making within the UK hotel sector. It aimed to explore how influencer marketing interacted with consumer psychology and digital behavior, with particular emphasis on trust, authenticity, and perceived expertise. Methodology : The research adopted a mixed-methods approach grounded in an interpretivist philosophy and inductive reasoning. Guided by the Engel-Kollat-Blackwell (EKB) model, the theory of planned behavior (TPB), source credibility theory, and the concept of social proof, primary data were collected through an online survey of 200 UK travelers and 12 in-depth interviews. Findings : The findings revealed that social media content had a significant influence on consumer choices at various stages of the decision-making process, particularly among younger demographics. Trust, authenticity, and perceived expertise of influencers emerged as decisive factors, while peer influence and fear of missing out (FOMO) also acted as strong motivators for some participants. Practical Implications : The study recommended that hospitality brands strategically collaborate with credible influencers whose values align with the brand, promote transparency in sponsorships, and incorporate user-generated content to enhance trust and booking conversions. Originality : This research uniquely integrated multiple theoretical models to provide a comprehensive understanding of influencer-driven decision-making in a high-involvement service context. By focusing on the UK hotel industry, it provided culturally specific insights that are often overlooked in broader, global hospitality research.